Analysis and Design of Responsive Web-Based Learning Media Equipped with Pomodoro Feature in the Course of Software Engineering - Patmanthara, Syaad; Perdana Putra, Muhammad Ricky; Soraya, Dila Umnia (Universitas Negeri Malang, 2024)
The development of information and communication technology has brought about changes in the field of education, one of which is the emergence of web-based learning. Based on preliminary observation data collected through questionnaires, students still expressed uncertainty about their understanding of software engineering (SE) materials. The current learning media for SE include PowerPoint (PPT), e-modules, and instructional videos, which students find less engaging and challenging to comprehend. Additionally, students face distractions like games and social media, leading to difficulty maintaining focus while studying. The objectives of this research are (1) to analyze user and system needs and (2) to design web-based responsive learning media for the software engineering course, equipped with a Pomodoro feature. The research method used is research and development (R and D) with the 4D Thiagarajan development model, consisting of four stages: define, design, develop, and disseminate. However, only the definition and design stages were carried out due to research limitations. The presentation of data analysis results involves (1) needs analysis, which includes frontend analysis, learner analysis, task analysis, concept analysis, and specifying instructional objectives; (2) system design, which includes context diagrams and data flow diagrams; (3) database design, which includes Entity Relationship Diagram (ERD) and database file structure; (4) initial design in the form of a prototype; (5) technology design for development and implementation; and (6) instructional media testing design